Otologic Manifestations in Patients with Achondroplasia: A Multicenter Study - Dohee Kim; Joonsik Yoon; Myung-Whan Suh; Jun Ho Lee; Moo Kyun Park (Journal of International Advanced Otology)
Background: Achondroplasia, the most prevalent form of skeletal dysplasia involving short stature, necessitates a multidisciplinary approach that includes otology and auditory rehabilitation. Despite this, the clinical characteristics of hearing loss and otologic manifestations in achondroplasia patients remain poorly defined. This study aimed to explore the prevalence and treatment outcomes of otologic disease in individuals with achondroplasia.